Identification of yellow rust resistance gene YR 24 in the collection material of winter soft wheat - N. N. Vozhzhova; N. T. Kupreyshvili; A. Yu. Myshastaya; A. A. Yatsyna; T. G. Derova; D. M. Marchenko (Зерновое хозяйство России, 2018)
Identification of yellow rust resistance gene Yr 24 in the collection material of winter soft wheat The yellow rust caused by the fungus Puccinia striiformis is one of three types of rust that affects wheat all over the world. During some years the yield loss caused by the fungus could become up to 5.5 million tons per year of the worldwide wheat yield. The use of the sources with efficient yellow rust resistance genes as initial material for breeding on tolerance to the disease is of great importance nowadays. The article presents the study results of 737 samples of the collection material of winter soft wheat with an identified yellow rust resistance gene Yr 24 that is efficient on the territory of the Southern Federal Area. The study has been carried out by the staff of the laboratory for molecular identification of the Federal State Budget Scientific Institution “Agricultural Research Center “Donskoy”. The percent of winter soft wheat infected with the fungus on the experimental fields of the laboratory of plant immunity and protection has been taken as a criterion of the assessment of the laboratory analysis. As a result we have identified 272 samples with a marker of an efficient yellow rust resistance gene Yr 24. We have found 28 samples with this gene, which possess a low level of infection (0-5%) in the conditions of artificial infection and thus can be recommended as the sources of the gene Yr 24 for the breeding programs directed on “resistance to diseases”.